The Study of Active Monitoring in Sweden (SAMS): A randomized study comparing two different follow-up schedules for active surveillance of low-risk prostate cancer. (October 2013) - Bratt, Ola; Carlsson, Stefan; Holmberg, Erik; Holmberg, Lars; Johansson, Eva; Josefsson, Andreas; Nilsson, Annika; Nyberg, Maria; Robinsson, David; Sandberg, Jonas; Sandblom, Dag; Stattin, Pär
Abstract Objective. Only a minority of patients with low-risk prostate cancer needs treatment, but the methods for optimal selection of patients for treatment are not established. This article describes the Study of Active Monitoring in Sweden (SAMS), which aims to improve those methods. Material and methods. SAMS is a prospective, multicentre study of active surveillance for low-risk prostate cancer. It consists of a randomized part comparing standard rebiopsy and follow-up with an extensive initial rebiopsy coupled with less intensive follow-up and no further scheduled biopsies (SAMS-FU), as well as an observational part (SAMS-ObsQoL). Quality of life is assessed with questionnaires and compared with patients receiving primary curative treatment. SAMS-FU is planned to randomize 500 patients and SAMS-ObsQoL to include at least 500 patients during 5 years. The primary endpoint is conversion to active treatment. The secondary endpoints include symptoms, distant metastases and mortality. All patients will be followed for 10–15 years. Results. Inclusion started in October 2011. In March 2013, 148 patients were included at 13 Swedish urological centres. Conclusions. It is hoped that the results of SAMS will contribute to fewer patients with indolent, low-risk prostate cancer receiving unnecessary treatment and more patients on active surveillance who need treatment receiving it when the disease is still curable. The less intensive investigational follow-up in the SAMS-FU trial would reduce the healthcare resources allocated to this large group of patients if it replaced the present standard schedule.